High‐Strength Frosted Glass by Ion Exchange of Float Glass with a Potassium Water Glass Film. (7th October 2015) - Patschger, Marek; Bocker, Christian; Rüssel, Christian
Abstract : Frosted glasses with increased strength were prepared by ion exchange process. Float glass samples with a size of approximately 7 × 7 cm 2 were spray‐coated with potassium water glass. After drying, the samples were thermally treated at 405°C for 20 h. This led to ion exchange of the sodium ions of the float glass for the potassium ions of the water glass layer. The remaining coating was not removed from the glass. At the interface coating/glass, a diffusion layer with a high potassium concentration is formed. The penetration depth is around 18 μm. The strength of the glass increased from 180 MPa for an uncoated glass to 290 MPa for the ion‐exchanged glass (measured with a double ring test). The glasses showed intense light scattering due to the remaining scratch‐resistant coating.